“You’ve got to look after yourself, to be able to look after them” a qualitative study of the unmet needs of caregivers of community based primary health care patients - Kuluski, Kerry (BMC Geriatr, 2018)
BACKGROUND: There is growing reliance on unpaid caregivers to provide support to people with care needs. Integrated care approaches that aim to coordinate primary care with community care known as community based primary health care (CBPHC) has been a key policy initiative across health systems; however most attention has been paid to the needs of patients and not caregivers. The objective of this paper was to explore the unmet needs of caregivers of older adults with complex care needs receiving CBPHC. METHODS: This qualitative descriptive study entailed one-to-one interviews with 80 caregivers from Canada and New Zealand where roles, experiences and needs were explored. Interview text related to unmet need was reviewed inductively and core themes identified. RESULTS: Three themes were identified across CBPHC sites: unrecognized role; lack of personal resources; and no breaks even when services are in place. CONCLUSIONS: To support caregivers, models of care such as CBPHC need to look beyond the patient to meaningfully engage caregivers, address their needs and recognize the insight they hold. This knowledge needs to be valued as a key source of evidence to inform developments in health and social care. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12877-018-0962-5) contains supplementary material, which is available to authorized users.